2021
DOI: 10.1111/jfpp.16218
|View full text |Cite
|
Sign up to set email alerts
|

Extraction optimization and functional properties of corn germ meal albumin protein as a potential source of novel food ingredients

Abstract: Albumin is the main component of the protein of corn germ meal (CGM). In this study, we first optimized the CGM albumin extraction condition at a 1:11 mass ratio of CGM to water, 2.5 hr extraction time, and 35°C extraction temperature, from which 38.05% of the extraction rate was achieved. FTIR analysis showed that the extracted CGM albumin contained typical amide A, B, I, II, and III protein bands. Functional properties showed that the CGM albumin exhibited a relatively high water‐holding capacity of 2.0 ml/g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…Ding et al ( 60 ) found that the trend of FC under other physical treatments was similar to that of heat treatment, which showed an upward trend with increasing intensity of physical conditions, followed by a downward trend. At the same time, we found that the heated albumins with over 85% of FC which was significantly higher than the corn germ meal albumin of FC (67%) ( 61 ).…”
Section: Resultsmentioning
confidence: 78%
“…Ding et al ( 60 ) found that the trend of FC under other physical treatments was similar to that of heat treatment, which showed an upward trend with increasing intensity of physical conditions, followed by a downward trend. At the same time, we found that the heated albumins with over 85% of FC which was significantly higher than the corn germ meal albumin of FC (67%) ( 61 ).…”
Section: Resultsmentioning
confidence: 78%